Pengaruh Permainan Tradisional Ular Naga Terhadap Perkembangan Aspek Kesadaran Diri Anak Usia 5-6 Tahun di TK Aisyiyah Bustanul Athfal 41 Kec. Medan Sunggal - Dini Komariah Rangkuti; Kamtini Kamtini (FKIP, Universitas Palangka Raya, 2025)
The problem with this research is the limited media and game tools, such as; Role playing and traditional games are still rarely applied by teachers in the learning/teaching process so that children easily get bored during learning/teaching activities. The aim of this research is to determine the significant influence of the traditional dragon snake game on the development of aspects of self-awareness in children aged 5-6 years at Kindergarten Aisyiyah Busthanul Athfal 41 Medan. This research uses Quasi Experimental Design with The Equivalent Time Sample Design. The subjects of this research were 28 children in the orchid class at ABA 41 Kindergarten. The sampling technique uses purposive sampling and the data analysis technique uses non-parametric statistical tests. The results of the data from this study show that the average value of the first treatment (X1) has an average value of 17.5, categorized as BSH (developing according to expectations), not given the first treatment (X0) has an average value of 14.0, categorized as BSH (developing). according to expectations), the second treatment (X2) had an average value of 18.46 in the BSH category (developed according to expectations), not being given the second treatment (X0) had an average value of 15.67 in the BSH category (developed according to expectations). The results of data analysis through the SPSS version 25 statistical test show that Asymp. Sig 0.000 < 0.05 hypothesis is accepted, it can be concluded that there is a significant influence of traditional games on the development of aspects of self-awareness in children aged 5-6 years at Kindergarten Aisyiyah Bustanul Athfal 41 Medan.